Transscleral Fixation of the Dislocated IOL-Capsular Bag Complex in Contraction Capsular Syndrome - D. I. Ivanov; V. N. Nikitin (Oftalʹmologiâ, 2022)
Contraction capsule syndrome is a serious complication accompanied by structural changes of the capsule bag. Fibrous changes of the lens capsule are found in the postoperative period, even in cases of uncomplicated primary cataract surgery. A certain influence has both general systemic state of the patient and local predisposing factors: the presence of pseudoexfoliative syndrome, the material and design of IOL, the size and shape of the anterior capsulorexis. The far-reaching pathological process leads to pronounced anatomical disorders. Excessive, asymmetrical fibrosis of the anterior capsule in combination with the capsulorexis phimosis leads to IOL decentration and frontal inclination, as well as to the dislocation of the entire IOL capsule complex due to local defects of the zinc ligament. The article presents the method of transscleral-suture fixation of the dislocated IOL-Capsular bag complex developed as a result of contraction capsule syndrome on clinical examples. Its distinctive advantages are described. Reduction of invasiveness is achieved due to the “one puncture” technique — ab externo, needle 30G. The proposed method is technically simple and reliable due to absence of conjunctiva peritomy, low probability of polypropylene 9-0 biodegradation, and possibility of its application with different IOL models allows to speak about its universality.